The Effect of Carbon Nanotube-Reinforced Polymer fins in Compact Heat Exchanger - Alshameri, M. H.; Azizuddin, Abd Aziz; Azim, Arshad; Sadeq, Safwan (Institute of Physics, 2025)
Carbon nanotube (CNT) reinforced polymer composites have shown great potential for the fabrication of compact fins-and-tube heat exchangers due to their excellent thermal and mechanical properties. The incorporation of 2% CNTs into the polymer matrix significantly enhances thermal conductivity and mechanical strength. Experimental results demonstrate a notable improvement in heat dissipation efficiency, with an overall heat transfer coefficient enhancement of up to 16%. The fins, measuring 120 mm wide, 120 mm long, and 2 mm thick, were successfully constructed and tested, resulting in a peak local heat transfer coefficient of 183.83 W/m²·°C. These findings suggest that CNT reinforced polymer fins can effectively serve as lightweight, corrosion-resistant alternatives to traditional metallic fins in heat exchanger applications.